Job satisfaction among general practitioners in private clinics in Tehran, Iran - Ebadi M; Montazeri A; Azin S.A; Shahidzadeh A; Harirchi A.M; Baradaran Moghadam H.R; Yourdkhani F (Payesh, 2005)
Objective(s): The objective of this study was to measure anxiety and depression in women undergoing diagnostic or screening mammography in a specialized breast cancer clinic. Methods: Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (RADS). A consecutive sample of women was entered into the study and the RADS was administered at their first clinic visit, before the diagnosis was made. Results: In all 1147 women completed the questionnaire. The results indicated that 27% of women suffer from severe anxiety and 14% from severe depressive symptoms. However, the mammography results indicated that only 7% of the women had suspicious lesions. There was no significant association between mammography-based diagnosis and severe anxiety or sever depressive symptoms. In addition, the findings showed that those who were younger and had lower level of education were more likely to suffer from server anxiety.  In contrast, old age and low education were associated with severe symptoms of depression. Conclusion: The results suggest that young and poorly educated elderly women need more attention when they are attending for mammography. The finding form present study also might contribute to improvements of the service is offered in order to reduce anxiety and depression.